Dental needs of elderly hostel residents in inner Melbourne - Saub, R.; Evans, R.W. (2001)
Background. The purpose of this study was to determine the oral health status and treatment needs of elderly hostel residents in Melbourne. Method: One hundred and seventy-five subjects aged 65+ were selected from 20 hostels within a 10km radius of Melbourne's central business district. Results: Subjects were clinically examined and interviewed using a standard questionnaire. In the course of the clinical examination, coronal caries, root caries, periodontal disease, denture status and related treatment needs were assessed. The mean age of the subjects was 83.7, the majority of whom were female (80 per cent). About 35 per cent of the sample were dentate. The mean number of teeth present among dentate persons was 13.8, the mean coronal caries experience was 24.9 DMFT and mean root caries was 2.3 R-DF Of the dentate subjects, 46 per cent required at least one restoration for coronal caries and 30 per cent required at least one restoration for root caries. Most dentate subjects had calculus and none had deep pockets, therefore, indications for periodontal treatment did not include complex care. More than 50 per cent of lower full dentures were retained unsatisfactorily and about half of the total number of subjects required prosthetic treatment. Conclusions: Although there was a high number of treatment needs, most requirements involved simple technologies that could be delivered by auxiliaries.